The Relationship between Lifestyle Factors and Obesity Indices among Adolescents in Qatar - Abdelhamid Kerkadi (10724304) (2019)
Background Physical inactivity, sedentary behaviour and an unhealthy diet are factors that may increase weight and general and/or abdominal obesity. Objective: To evaluate the relationship between general and abdominal obesity and lifestyle factors among adolescents in Qatar. Methods The study data are based on the Arab Teens Lifestyle Study (ATLS). The target population consisted of 1184 adolescents aged between 14 and 18 years old (563 boys and 621 girls), randomly selected through multistage sampling. A validated questionnaire was used to collect data on lifestyle indicators. Anthropometric indicators, which included body weight, height and waist circumference (WC), were measured according to standardised procedures. International Obesity Task Force (IOTF) age- and sex-specific body mass index (BMI) reference values were used to define overweight and obesity. Abdominal obesity was defined by the ‘waist-to-height ratio’ (WHtR > 0.5) and by sex- and age-specific WC cutoff values. Results Females were more inactive than males (63.7% vs. 36.3%; p < 0.001). The proportion of adolescents who reported screen time of over 2 h per day was 82.5%. Females engaged in more sedentary behaviour than males (53.4% vs. 46.4%, p = 0.009). Being male (OR: 1.3; CI: 1.0–1.7) and skipping breakfast (OR: 1.5; CI: 1.2–2) were significantly associated with overweight/obesity. In contrast, high intake of fast food, fries, sweets and cake were negative predictors of general and abdominal obesity. Conclusions The findings revealed the prevalence of unhealthy lifestyle habits among adolescents in Qatar and indicated relationships between certain dietary habits and obesity. The findings of this study may help in advocating for the implementation of an intervention that includes lifestyle changes targeting adolescents. Other Information Published in: International Journal of Environmental Research and Public Health License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijerph16224428